A Comparative Study Between Two Monitoring Techniques Of Awake Blind Nasal Intubations In Cases Of Restricted Mouth Opening (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Intubating a patient with limited or nil mouth opening is always a challenge,  particularly when fibreoptic laryngoscope is not available. Awake Blind Nasotracheal  Intubation[ABNI] is one of the options for intubating such patients. It requires sufficient patient  cooperation and comfort. Presently available short acting analgesics and amnesias are excellent  choices for this exercise. Aims: The present study was to compare the two techniques while performing nasotracheal  intubation: monitoring by spontaneous respiratory movement in rebreathing bag of breathing  circuit, with monitoring by EtCO2 tubing attached to breathing circuit while performing [ABNI]. Study Design: This prospective randomized study of 60 patients undergoing Commando surgery  with anticipated difficult airway. They were randomly assigned into two groups of 30 each  according to the method used for [ABNI]. After complete airway block, Group (A) patients were  monitored by spontaneous respiratory movement in rebreathing bag of breathing circuit while  performing [ABNI] and while Group (B) patients were monitored by EtCO2 tubing attached to  breathing circuit while performing [ABNI]. 20 patients were intubated at first attempt, 6 at  second and 4 patients at third attempt in Group A, while 21were intubated at first, 5 at second  and 4 at third attempt in Group B. These differences were insignificant. The mean time  required for successful intubation was in Group A (2.47± 0.068) min. and in Group B  (2.42±0.057) min. which was insignificant. Also, success rate, hemodynamic changes and  complications and severity score were comparable in both groups. In conclusion: This study showed that both the techniques in performing [ABNI] are equally  valuable. There was no significant difference between the success rates of both techniques.[ABNI] under topical anesthesia may provide an alternative safe method in anticipated difficult  intubation, particularly if fiberoptic bronchoscope is not available.
Keywords: Intubation; Awake blind nasal; Two monitoring techniques